2017
DOI: 10.1212/wnl.0000000000004185
|View full text |Cite
|
Sign up to set email alerts
|

Prospective clinical and DaT-SPECT imaging in premotor LRRK2 G2019S-associated Parkinson disease

Abstract: Objective: To assess the value of baseline clinical and imaging biomarkers in a cohort of asymptomatic LRRK2 G2019S carriers for predicting conversion to Parkinson disease (PD) at 4 years.Methods: Thirty-two asymptomatic carriers of LRRK2 G2019S mutation underwent baseline and Results: Three carriers, asymptomatic at baseline, had converted to PD at 4-year evaluation.Twenty-three participants were fully evaluated. PD converters had lower striatal DaT binding at baseline than nonconverters (p 5 0.002). A baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 19 publications
2
37
1
Order By: Relevance
“…Variable neuropathological substrates, even in the same kindreds as has been well documented to occur in cases with other pathogenic LRRK2 mutations, could explain this finding. A decline in DaT‐SPECT ( 123 I‐ioflupane) binding has been previously suggested to be a useful tool to predict phenoconversion in LRRK2‐NMC . In our study two of three (66.7%) LRRK2‐NMC with a positive RTQuIC had an abnormal DaT‐SPECT result, whereas this occurred only in two of 13 (15.3%) of the negative ones.…”
Section: Discussionmentioning
confidence: 43%
“…Variable neuropathological substrates, even in the same kindreds as has been well documented to occur in cases with other pathogenic LRRK2 mutations, could explain this finding. A decline in DaT‐SPECT ( 123 I‐ioflupane) binding has been previously suggested to be a useful tool to predict phenoconversion in LRRK2‐NMC . In our study two of three (66.7%) LRRK2‐NMC with a positive RTQuIC had an abnormal DaT‐SPECT result, whereas this occurred only in two of 13 (15.3%) of the negative ones.…”
Section: Discussionmentioning
confidence: 43%
“…Dopaminergic imaging abnormalities were also found in some (but not all) studies of at‐risk PD gene carriers, providing additional indirect evidence of predictive value . A small prospective study documented predictive value of DAT scanning in asymptomatic LRRK2 carriers . So far, based on estimates from the PARS study, dopaminergic PET/SPECT is the strongest neuroimaging marker (relative risk = 17), making it second only to RBD in predictive value for prodromal PD …”
Section: Key Advances In the Last Decadementioning
confidence: 98%
“…Predictive value was confirmed in other population‐based studies, although RR were lower (RR = 8.1 and 7.9). Studies in LRRK2 cohorts also found high prevalence of SNpc abnormalities, providing indirect evidence of predictive value (albeit with no clear predictive value in a small prospective follow‐up). Intriguingly, patients with melanoma (a risk factor for PD) had higher rates of hyperechogenicity, an effect that was partially explained by skin pigmentation .…”
Section: Key Advances In the Last Decadementioning
confidence: 99%
See 1 more Smart Citation
“…Once manifest, the motor features of LRRK2 ‐PD are largely indistinguishable from idiopathic PD, and examination of carriers of LRRK2 mutations therefore provide a useful model for prodromal PD. In the last few years, several longitudinal cohort studies of LRRK2 carriers have been published (Mestre et al., ; Mirelman et al., , ; Pont‐Sunyer et al., ; Sierra et al., , ). However, unlike in “idiopathic” PD, anosmia has been reported to be infrequent in LRRK2 PD cases (Marras et al., ) and also in LRRK2 carriers (Mestre et al., ; Mirelman et al., ; Pont‐Sunyer et al., ).…”
Section: Lrrk2mentioning
confidence: 99%